2019
DOI: 10.1177/1077699019876634
|View full text |Cite
|
Sign up to set email alerts
|

News on Facebook: How Facebook and Newspapers Build Mutual Brand Loyalty Through Audience Engagement

Abstract: Focused on the value of Facebook as a distribution platform for newspapers, this study shows that news which attracts and holds readers’ attention on Facebook is positively related to the brand awareness and brand loyalty of newspapers and Facebook. Brand-wise, Facebook and newspapers benefit when news is distributed through Facebook. The study shows that Facebook and major newspapers are somewhat mutually beneficial in helping build the brand loyalty of both. However, audiences who read news from major brands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 44 publications
(101 reference statements)
0
9
0
3
Order By: Relevance
“…After deducting the Facebook live videos, video news, blogs, and other non-textual posts 105 news and reports were collected as samples from the websites of the news organizations after fetching the source link from Facebook pages. As one of the objectives of the study is to find how these news organizations promote news via their Facebook pages as their brand value as a news organization is connected with social media news shares (Al-Rawi, 2017a; Chen & Pain, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…After deducting the Facebook live videos, video news, blogs, and other non-textual posts 105 news and reports were collected as samples from the websites of the news organizations after fetching the source link from Facebook pages. As one of the objectives of the study is to find how these news organizations promote news via their Facebook pages as their brand value as a news organization is connected with social media news shares (Al-Rawi, 2017a; Chen & Pain, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…While Strömbäck et al [ 38 ] substantiated knowledge as a strong predictor of active news use, Leonhard et al [ 39 ] revealed that some users are less willing to invest actively into staying informed about current news. On the contrary, Chen and Pain [ 40 ] identified the concept of social media news engagement regardless of topic-related dimensions, reducing it to two dimensions: content-interaction engagement and exposure engagement. We cannot limit it to users’ habits, i.e., solely as “action-driven” social media news engagement.…”
Section: Methodsmentioning
confidence: 99%
“…El segundo gran objetivo que cubren las investigaciones dedicadas al engagement es entender el consumo de noticias como condición necesaria pero no suficiente para conseguir el engagement del público. El consumo de noticias en internet se da mayoritariamente a través de redes sociales, donde el usuario está más expuesto a fuentes no fiables (Chen;Pain, 2019). El análisis del comportamiento del usuario en Facebook es el más frecuente en los estudios.…”
Section: Julio-diciembre De 2022unclassified
“…Pese al esfuerzo de los medios por estar presentes allá donde está la audiencia, la fidelidad se genera hacia la página de Facebook de los medios, no hacia los medios (Chen;Pain, 2019). Por ello, los medios son cada vez más conscientes de que la presencia en redes no es la solución a su crisis de relevancia.…”
Section: Julio-diciembre De 2022unclassified
See 1 more Smart Citation